2011
DOI: 10.1074/jbc.m111.258798
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidate Phosphatase Activity Plays Key Role in Protection against Fatty Acid-induced Toxicity in Yeast

Abstract: The PAH1-encoded phosphatidate (PA) phosphatase in Saccharomyces cerevisiae is a pivotal enzyme that produces diacylglycerol for the synthesis of triacylglycerol (TAG) and simultaneously controls the level of PA used for phospholipid synthesis. Quantitative lipid analysis showed that the pah1⌬ mutation caused a reduction in TAG mass and an elevation in the mass of phospholipids and free fatty acids, changes that were more pronounced in the stationary phase. The levels of unsaturated fatty acids in the pah1⌬ mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
185
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(199 citation statements)
references
References 109 publications
12
185
0
2
Order By: Relevance
“…Recently, it has been reported that deletion of yeast phosphatidate phosphatase makes the cells more sensitive to fatty acid-induced toxicity (38), a finding that concurs with the results presented here. Yeast possesses only one gene coding for phosphatidate phosphatase, whereas mammals possess three genes that encode for lipin proteins, and one of them, Lpin1, undergoes alternative splicing to generate two more lipin variants in mouse (lipin-1␣ and -1␤) and three in humans (lipin-1␣, -1␤, and -1␥).…”
Section: Discussionsupporting
confidence: 82%
“…Recently, it has been reported that deletion of yeast phosphatidate phosphatase makes the cells more sensitive to fatty acid-induced toxicity (38), a finding that concurs with the results presented here. Yeast possesses only one gene coding for phosphatidate phosphatase, whereas mammals possess three genes that encode for lipin proteins, and one of them, Lpin1, undergoes alternative splicing to generate two more lipin variants in mouse (lipin-1␣ and -1␤) and three in humans (lipin-1␣, -1␤, and -1␥).…”
Section: Discussionsupporting
confidence: 82%
“…The increase in membrane lipid content was also observed in tgd1-1 disrupted in PDAT1 (Fan et al, 2013a) and in yeast mutants defective in TAG synthesis (Petschnigg et al, 2009;Fakas et al, 2011). Such an increase has been regarded as an alternative means to protect against lipotoxicity due to lipid overload (Petschnigg et al, 2009;Fakas et al, 2011).…”
Section: Fa B-oxidation Is Important For Cellular Lipid Homeostasismentioning
confidence: 74%
“…The increase in membrane lipid content was also observed in tgd1-1 disrupted in PDAT1 (Fan et al, 2013a) and in yeast mutants defective in TAG synthesis (Petschnigg et al, 2009;Fakas et al, 2011). Such an increase has been regarded as an alternative means to protect against lipotoxicity due to lipid overload (Petschnigg et al, 2009;Fakas et al, 2011). Because phospholipid levels are elevated in both tgd1-1 sdp1-4, in which TAG hydrolysis is impaired, and tgd1-1 pxa1-2, in which FA degradation is impaired, it is unlikely that this increase is due to the augmented recycling to TAG into membrane lipids as a result of blocked FA turnover.…”
Section: Fa B-oxidation Is Important For Cellular Lipid Homeostasismentioning
confidence: 85%
See 1 more Smart Citation
“…stationary phase) (6). Moreover, PA and DAG serve as signaling molecules that control transcription, membrane proliferation, vesicular trafficking, and the activation of cell growth (7-16).Disturbing the PA/DAG balance in yeast, as caused by the lack of Pah1 PA phosphatase activity, results in the abnormal regulation of phospholipid synthesis gene expression and phospholipid content, the aberrant growth of the nuclear/ER membrane, vacuole fragmentation, a defect in lipid droplet formation, an acute sensitivity to fatty acid-induced toxicity, and a reduction in chronological life span (1,3,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Of the cellular defects imparted by the pah1⌬ mutation, those related to the elevated PA content are dependent on Dgk1 DAG kinase activity and are mimicked by the overexpression of DGK1 (1,3,6,18,21,23,25,27).…”
mentioning
confidence: 99%